Does the Suitability of National Culture Matters in the Adoption of Six Sigma? - Qamar, Ahsan; ., Ahmad Jusoh; ., Halimah Idris (Information Management and Business Review, 2013)
The concept and methodology of Six Sigma was developed by the American companies within the local culture of America. Therefore it is grounded on the standards, ethics and behaviours represented by America. The present study proposes that implementing Six Sigma in other countries with different cultures, norms and behaviours may have adjustment problems, as the required culture, values and behaviours for Six Sigma do not match with the local cultures of countries. A conceptual model is proposed which would utilize the Hofstede’s cultural dimensions to determine the effect of national culture at each phase of Six Sigma process.